The influence of risk and uncertainty on teachers' responses to professional learning and development. Issue 2 (19th April 2017) - Twyford, Kaye; Le Fevre, Deidre; Timperley, Helen
Abstract : Purpose: The purpose of this paper is to explore how perceptions of risk influenced teachers' sensemaking and actions during a professional learning and development (PLD) initiative where teachers were expected to change their practices. Design/methodology/approach: A risk perception lens, focussed on uncertainty, was used to capture the on-going experiences of teachers as they participated in PLD. The PLD, delivered by one organisation, focussed on developing teacher use and understanding of formative assessment practices. Data for this three-school qualitative exploratory case study of teachers' perceptions of risk primarily utilised qualitative interviews. Findings: Findings identified that teachers perceived risk and experienced feelings of vulnerability as a result of their on-going assessment and evaluation of the uncertainty in the professional learning context. The perceived risk informed teachers' responses and actions, ultimately impacting on teachers' learning. Practical implications: The risk perception process model developed from the findings and conceptual framework provides a tool for educators to navigate and reduce perceived risk and enhance learning in change. Originality/value: This research advances the conceptualisation of perceived risk in PLD. It challenges the current concept of teachers' resistance and instead considers the role of their perceptions of risk, broadening the understanding of responses to educational change.